2014
DOI: 10.4103/2231-0762.146212
|View full text |Cite
|
Sign up to set email alerts
|

Pathognomonic features of Angle′s Class II division 2 malocclusion: A comparative cephalometric and arch width study

Abstract: Background:A thorough knowledge of the salient features of malocclusion helps the clinician in arriving at a proper diagnosis and treatment plan, and also to predict the prognosis, prior to the onset of treatment process. Among the four classes of Angle's classification of malocclusion, Class II division 2 occurs with the least frequency. There is still continuing debate in the literature whether the Class II division 2 patients ascribe the pathognomonic skeletal and dental features.Aim of the study:The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…While the morphological development of the tooth crown is predominantly under genetic control, but the root form appears to be influenced by local environmental factors. 29 The skeletal and the tooth size characteristic appearance in Class II division 2 malocclusion cases is uniquely influenced by genetic component as suggested by Peck et al and Fourneron et al 30,31 Some pathognomonic features of Class II division 2 malocclusion as described by Prasad et al were similar to those observed by Peck et al 32 Some dental anomalies are associated with Class II division 2 malocclusion but it is not common in all types of Class II Division 2 malocclusion as reported by Pereira et al and Basdra et al 33,34 Any alteration in the function during root formation may cause variations in the axis of crown and root because of different sequence of crown and root development. 35 A normal collum angle which is most often seen in the central incisors of Class I and Class II division 1 could be because of physiological pressure from the tongue on the lingual side and lips on the labial side which results in the proper eruptive guidance as reported by Harris et al 17 For torque expression collum angle is critically important when using a straight wire appliance.…”
Section: Discussionmentioning
confidence: 71%
“…While the morphological development of the tooth crown is predominantly under genetic control, but the root form appears to be influenced by local environmental factors. 29 The skeletal and the tooth size characteristic appearance in Class II division 2 malocclusion cases is uniquely influenced by genetic component as suggested by Peck et al and Fourneron et al 30,31 Some pathognomonic features of Class II division 2 malocclusion as described by Prasad et al were similar to those observed by Peck et al 32 Some dental anomalies are associated with Class II division 2 malocclusion but it is not common in all types of Class II Division 2 malocclusion as reported by Pereira et al and Basdra et al 33,34 Any alteration in the function during root formation may cause variations in the axis of crown and root because of different sequence of crown and root development. 35 A normal collum angle which is most often seen in the central incisors of Class I and Class II division 1 could be because of physiological pressure from the tongue on the lingual side and lips on the labial side which results in the proper eruptive guidance as reported by Harris et al 17 For torque expression collum angle is critically important when using a straight wire appliance.…”
Section: Discussionmentioning
confidence: 71%
“…The classification is based on axial inclination of upper anteriors. As mentioned in previous literature, class I division found to be more common in comparison to class II division (Indukuri et al, 2014). Dental arch form is the arch formed by the buccal and facial surfaces of the teeth when viewed from their occlusal surfaces (Dinesh et al, 2013).…”
Section: Introductionmentioning
confidence: 84%